The Depiction of Social Difference in Harper Lee's To Kill a Mockingbird - Westfál, David (Univerzita Pardubice, 2021)
This bachelor thesis aims to find and analyse the depiction of social differences in Harper Lee's To Kill a Mockingbird. It is divided into two parts, the first of which is theoretical and provides historical and sociological background on the lives of the Southern Americans in the first half of the twentieth century, focusing on the era of the Great Depression. The analytical part describes the social relations between Maycomb residents and their differentiation in language and examines the variety of housing and clothes regarding the social class.
Vyobrazení společenských rozdílů v knize Jako zabít ptáčka od Harper Lee
Keywords: společenská třída; americký jih; Lee, Harper; Velká hospodářská krize; social class; American South; Lee, Harper; Great Depression